The cup fungus Pestalopezia brunneopruinosa is Pestalotiopsis gibbosa and belongs to Sordariomycetes. - Kyoko Watanabe; Shunsuke Nozawa; Tom Hsiang; Brenda Callan (PLoS ONE)
Pestalopezia brunneopruinosa, the type species of Pestalopezia in Leotiomycetes, produces typical cup-shaped ascomata. Because its asexual morph has conidia comprised of five cells including apical and basal appendages and three pigmented median cells, it was first described as Pestalotia gibbosa, which belongs to Sordariomycetes. This contradiction has not been resolved due to the difficulty in isolating this fungus in culture. In this study, we isolated separate strains from the sexual morph and the asexual morph for molecular analysis. Phylogenetic trees of Sporocadaceae based on internal transcribed spacer, partial β-tubulin, and partial translation elongation factor 1-alpha sequence datasets revealed that both strains fall into the same taxon, in a clade in Pestalotiopsis sensu stricto alongside P. gaultheriae and P. spathulata. We provide the first evidence that fungi producing cup-shaped ascomata in Pestalotiopsis belong to Sordariomycetes, and we have proposed the transfer of Pestalopezia brunneopruinosa to Pestalotiopsis gibbosa.